Postfire Residual Strength and Morphology of Concrete Incorporating Natural Rubber Latex Exposed to Elevated Temperatures - Paul O. Awoyera; Hadee Mohammed Najm; Olusegun David Adefarati; Moutaz Mustafa A. Eldirderi; Khaled Mohamed Khedher; Husam Al Dughaishi; Jawad Al Lawati; Abdalrhman Milad (Advances in Civil Engineering)
The exposure of concrete to elevated temperatures is known to cause diverse severe damages in concrete composites. Hence, measures to improve the performance of concrete during exposure to fire are continually proposed. The present study investigated the postfire residual strength and morphology of concrete incorporating natural rubber latex exposed to elevated temperature. Four different concrete mixes were considered for the investigation, namely, a control sample made without natural rubber latex, the second sample containing 1% natural rubber latex, the third sample containing 1.5% natural rubber latex, and the fourth sample containing 3% of natural rubber latex. The concrete samples (150 mm cubes and 100 × 200 mm cylinders) were exposed to varying temperatures 300°C, 800°C, and 1000°C, after the curing process. Nondestructive tests using Schmidt rebound hammer and ultrasonic pulse tester were carried out on samples. The compressive strength and split-tensile strength of concrete cubes and cylinders, respectively, were determined. Micrographs and elemental distribution in the sample were studied using the scanning electron microscopy (SEM-EDX) apparatus. It could be seen from the results that the concrete strength properties reduced as the exposure temperature increased. The results also showed that NRL could be sparingly utilized as a concrete admixture, at 1% content. The performance of concrete was not stable at over 300°C when NRL addition was above 1%.